Prevalence and risk factors of urinary incontinence during antenatal period in women delivering in a tertiary care center of Northern India - Priya, Bhanu; Singh, Nilanchali; Rajaram, Shalini (International Journal Of Community Medicine And Public Health, 2017)
Background: Urinary incontinence (UI) is a commonly encountered entity in antenatal and postpartum period. It is known to have detrimental effects on quality of life in approximately 54.3% of all pregnant women. However, the true prevalence of UI is still not known, especially in the South East Asia. This study has investigated the prevalence and risk factors of urinary incontinence during antenatal period. Methods: 500 women admitted in postnatal ward were interviewed retrospectively about the UI occurred during antenatal period, using questionnaire. The study was done over a period of six months. Detailed information regarding risk factors of urinary incontinence was included in questionnaire based on previous validated studies. Data was analyzed using SPSS 20 using chi square test. P value <0.05 was taken as significant. Results: Total 500 women were interviewed and based on questionnaire. 202 reported incontinence, thus giving a prevalence of 40.4%, out of that 192 (45.5%) had stress urinary incontinence (SUI), 40(19.8%) had urge urinary incontinence (UUI) and 70 (34.6%) had mixed incontinence. The risk factors like bladder infections and chronic cough had significant association with urinary incontinence. Advancing gestation had worsening effects on the symptoms of UI (p =0.000). Conclusions: Urinary incontinence is a common and neglected problem with poor treatment seeking behavior. SUI is more common in pregnant women than urge or mixed incontinence. Obstetricians need to ask have precise interrogation regarding UI in pregnant women to diagnose and treat the problem.